Circulation and Exchanges at High-latitude Ocean Margins: Dynamical models and Observations from Instrumented Seals - Zhou, Qin (Universitetet i Tromsø, 2014)
Paper 2 and 3 of this thesis are not available in Munin: 2. Q. Zhou, T. Hattermann, O.A. Nøst, M. Biuw, K. V. Kovacs, C. Lydersen: 'Winddriven spreading of fresh surface water beneath ice shelves in the Eastern Weddell Sea' (manuscript). 3. Q. Zhou and Q. Shu: 'The e ect of wave-induced mixing in a coupled ocean-ice model in the Southern Ocean' (manuscript) Circulation and exchange processes at high-latitude ocean margins are investigated in this thesis, by using analytical models, numerical simulations and hydrographic data. In the Northern Hemisphere, the establishment of Atlantic Water transport as a topographically steered slope current has been investigated. A simplified analytical model based on geostrophic balance predicts that buoyancy loss over a sloping boundary leads to a cross-slope baroclinic flow transformed into an along-slope barotropic flow. And the resulting transport changes can be estimated from hydrographic data. Over the continental slope off Scotland, the diagnosed transport changes in the barotropic flow is in agreement with the observed transport changes. The results emphasize that geostrophy can be used to diagnose topographically steered barotropic flow, which makes it especially useful for high latitudes where topographic steering of ocean circulation is strong. In the Eastern Weddell Sea in the Atlantic Sector of Antarctica, the processes controlling the exchanges of water masses over the continental slope have been studied, by taking advantage of over 11,000 hydrographic profiles collected by instrumented seals in this region from February to November 2008. The proposed mechanism, that the wind-driven downwelling is responsible for the accumulation of Antarctic Surface Water near the ice front and its further spreading beneath the ice shelf along the coast of Eastern Weddell Sea, is revisited by a combination of detailed analysis of the data collected by the seals, an analytical model and numerical simulations. The results show that the Antarctic Surface Water enters the ice shelf ...